PENERAPAN IDENTIFIKA SUBSPACE DAN PERANCANGAN KONTROL PREDIKTIF PADA WASTE HEAT BOILER (WHB) - Hamduria Faulin, Luke
Waste Heat Boiler (WHB) system, representing one type of boiler system which using heat transfer energy from gas turbine exhaust gas flow. More than a half or exactly about 60% of 70% of the heat that obtained by combustion in gas turbine, re-exploited by WHB to help obtaining the steam. Several problems as the change of temperature of the exhaust gas and the change of level drum may be affecting to the steam. Specification and performance system as a whole must also preserved with considering the operation constraints on the square. The representation of evaluated WHB system has three inputs and one of measured disturbance that influencing five outputs as a whole. These representations assumed as a form of multivariable system representation, where the variables of the system interrelated. The beginning stage in this research is modeling the WHB system by multivariable system representation, using subspace identification approach. The subspace term representing the reflection of linear model equation form, which calculated to row and column of the input-output matrices. Then, the model of identification results will be used in predictive control designing. Some reason and also the consideration in predictive control usage is economic, safety and environmental, instrument operation constraint factor, and also product quality factor. The bases of predictive control problems include the process and disturbance model, performance index, constraint handling, optimization and also receding horizon principal (prediction and control moveWaste Heat Boiler (WHB) system, representing one type of boiler system which using heat transfer energy from gas turbine exhaust gas flow. More than a half or exactly about 60% of 70% of the heat that obtained by combustion in gas turbine, re-exploited by WHB to help obtaining the steam. Several problems as the change of temperature of the exhaust gas and the change of level drum may be affecting to the steam. Specification and performance system as a whole must also preserved with considering the operation constraints on the square. The representation of evaluated WHB system has three inputs and one of measured disturbance that influencing five outputs as a whole. These representations assumed as a form of multivariable system representation, where the variables of the system interrelated. The beginning stage in this research is modeling the WHB system by multivariable system representation, using subspace identification approach. The subspace term representing the reflection of linear model equation form, which calculated to row and column of the input-output matrices. Then, the model of identification results will be used in predictive control designing. Some reason and also the consideration in predictive control usage is economic, safety and environmental, instrument operation constraint factor, and also product quality factor. The bases of predictive control problems include the process and disturbance model, performance index, constraint handling, optimization and also receding horizon principal (prediction and control moveWaste Heat Boiler (WHB) system, representing one type of boiler system which using heat transfer energy from gas turbine exhaust gas flow. More than a half or exactly about 60% of 70% of the heat that obtained by combustion in gas turbine, re-exploited by WHB to help obtaining the steam. Several problems as the change of temperature of the exhaust gas and the change of level drum may be affecting to the steam. Specification and performance system as a whole must also preserved with considering the operation constraints on the square. The representation of evaluated WHB system has three inputs and one of measured disturbance that influencing five outputs as a whole. These representations assumed as a form of multivariable system representation, where the variables of the system interrelated. The beginning stage in this research is modeling the WHB system by multivariable system representation, using subspace identification approach. The subspace term representing the reflection of linear model equation form, which calculated to row and column of the input-output matrices. Then, the model of identification results will be used in predictive control designing. Some reason and also the consideration in predictive control usage is economic, safety and environmental, instrument operation constraint factor, and also product quality factor. The bases of predictive control problems include the process and disturbance model, performance index, constraint handling, optimization and also receding horizon principal (prediction and control moveWaste Heat Boiler (WHB) system, representing one type of boiler system which using heat transfer energy from gas turbine exhaust gas flow. More than a half or exactly about 60% of 70% of the heat that obtained by combustion in gas turbine, re-exploited by WHB to help obtaining the steam. Several problems as the change of temperature of the exhaust gas and the change of level drum may be affecting to the steam. Specification and performance system as a whole must also preserved with considering the operation constraints on the square. The representation of evaluated WHB system has three inputs and one of measured disturbance that influencing five outputs as a whole. These representations assumed as a form of multivariable system representation, where the variables of the system interrelated. The beginning stage in this research is modeling the WHB system by multivariable system representation, using subspace identification approach. The subspace term representing the reflection of linear model equation form, which calculated to row and column of the input-output matrices. Then, the model of identification results will be used in predictive control designing. Some reason and also the consideration in predictive control usage is economic, safety and environmental, instrument operation constraint factor, and also product quality factor. The bases of predictive control problems include the process and disturbance model, performance index, constraint handling, optimization and also receding horizon principal (prediction and control moveWaste Heat Boiler (WHB) system, representing one type of boiler system which using heat transfer energy from gas turbine exhaust gas flow. More than a half or exactly about 60% of 70% of the heat that obtained by combustion in gas turbine, re-exploited by WHB to help obtaining the steam. Several problems as the change of temperature of the exhaust gas and the change of level drum may be affecting to the steam. Specification and performance system as a whole must also preserved with considering the operation constraints on the square. The representation of evaluated WHB system has three inputs and one of measured disturbance that influencing five outputs as a whole. These representations assumed as a form of multivariable system representation, where the variables of the system interrelated. The beginning stage in this research is modeling the WHB system by multivariable system representation, using subspace identification approach. The subspace term representing the reflection of linear model equation form, which calculated to row and column of the input-output matrices. Then, the model of identification results will be used in predictive control designing. Some reason and also the consideration in predictive control usage is economic, safety and environmental, instrument operation constraint factor, and also product quality factor. The bases of predictive control problems include the process and disturbance model, performance index, constraint handling, optimization and also receding horizon principal (prediction and control move